2015
DOI: 10.1007/s10973-015-4421-7
|View full text |Cite
|
Sign up to set email alerts
|

Study on the thermal decomposition of crocidolite asbestos

Abstract: The thermal behaviour of two crocidolite asbestos samples was characterized. Infrared spectroscopy (FT-IR), powder X-ray diffraction, scanning electron microscopy and thermal analysis (DTA and TG) with evolved gas analysis were carried out on samples of crocidolite asbestos as received and after heating in order to observe their structural changes and dehydroxylation process. The results show that the dehydroxylation process of crocidolite asbestos occurs at different temperatures and is in the range 400-650°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
4
13
0
1
Order By: Relevance
“…This is pseudomorph of crocidolite asbestos after its thermal decomposition and dehydroxylation process. However, the temperature 700°C is sufficient for the thermal decomposition of crocidolite, which was confirmed by previous studies [39], where was found that crocidolite asbestos undergoes dehydroxylation process in the temperature range 400-450°C. Because the in situ diffraction experiment (HT-XRD) was carried out in dynamic conditions, this observation suggests that calcination of cement-asbestos at 700°C should already be sufficient for thermal utilisation of asbestos-containing materials.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This is pseudomorph of crocidolite asbestos after its thermal decomposition and dehydroxylation process. However, the temperature 700°C is sufficient for the thermal decomposition of crocidolite, which was confirmed by previous studies [39], where was found that crocidolite asbestos undergoes dehydroxylation process in the temperature range 400-450°C. Because the in situ diffraction experiment (HT-XRD) was carried out in dynamic conditions, this observation suggests that calcination of cement-asbestos at 700°C should already be sufficient for thermal utilisation of asbestos-containing materials.…”
Section: Resultssupporting
confidence: 84%
“…In this case lower water absorption was obtained in comparison to the reference material (2.7 vs. 3.3 %). Also, the value of open porosity was the lowest [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] MPa, thus the standard requirements are fulfilled. It should be noted that the addition of 10 wt% of cement-asbestos did not reduce the compressive strength of ceramic material as compared to the sample with 5 wt% of this waste.…”
Section: Recycling Of the Transformation Product In Clinker Brick MIXmentioning
confidence: 99%
“…Dicalcium silicate (belite) Ca 2 SiO 4 and a small amount of ettringite 3CaO•Al 2 O 3 •3CaSO 4 •32H 2 O were also identified [24]. The material was calcined at 700°C for 2 h, then ground in a ball mill for 4 h. The calcination temperature was chosen to ensure thermal decomposition (dehydroxylation process) of the asbestos minerals [27,28] contained in the cement-asbestos and, on the other hand, to limit the thermal decomposition of calcite, which occurs at a temperature range of 800 to 900°C. To confirm the thermal decomposition of asbestos minerals included in the cement-asbestos material, material obtained after calcination was studied by the FT-IR method and compared with the IR spectrum of raw cement-asbestos (Figure 3).…”
Section: Experimental Characteristics Of the Used Raw Materialsmentioning
confidence: 99%
“…Asbestos minerals can be decomposed by dehydroxylation and recrystallization at temperatures that depend on mineral type [2]. Thermal decomposition of chrysotile theoretically follows the reaction path given below [6] …”
mentioning
confidence: 99%
“…In the study, chrysotile was fully decomposed into sellaite (MgF 2 ) and magnesium silicofluoride (MgSiF 6 ) by reaction with the acidic gas at 150 • C for 30 min. Tabata et al [16] proposed an asbestos decomposition method using recycled supernatant obtained from fly ash treatment with sulfur, Ca(OH) 2 , and water at 0.6 MPa at 160 • C for 1-2 h. The supernatant was mixed with asbestos in a ball mill at room temperature. After mixing, more than 99.9% of asbestos was decomposed.…”
mentioning
confidence: 99%